MODIFIKASI KOEFISIEN DAYA DUKUNG AKSIAL PONDASI TIANG BERDASARKAN BACK ANALYSIS PADA DATA LOADING TEST - Fauzi Lukman Najib; Herwan Dermawan; Rakhmat Yusuf (Kokoh, 2022)
The axial bearing capacity of the pile foundation is needed to determine the number of foundations required to carry the structural load. Calculation of the axial bearing capacity pile foundation produces a carrying capacity different from the results of loading tests in the field. The difference between the bearing capacity design with loading test result can make a waste of the number of poles used. To make effective use of the number of piles, the bearing capacity design is necessary to modify the coefficient so that bearing capacity design  is closer to the results of the loading test. The result of the modification the bearing capacity of the clay soil in an increase that is not much different from the initial coefficient but is strongly influenced by the value of the internal friction angle which can make the coefficient increase twice. For cohesionless soil, ultimate  base resistance  there is an average value of 56.75 tsf for N-SPT 50.